Speaking Performance and Grammatical Competence Across Cognitive Learning Styles and Strategy Inventory for Language Learning - Ayu Chandra Agustin; Ekaning Dewanti Laksmi; Suharyadi Suharyadi (Pascasarjana Universitas Negeri Malang, 2021)
Abstract: This study is an attempt to see the correlation between speaking performance and grammatical competence, particularly in the EFL context by including cognitive learning styles and Strategy Inventory for Language Learning (SILL). The correlational study is employed to analyze the scores of argumentative speaking and written grammar tests of 30 Economics students at STIE Malangkuceswara Malang. It is found that there is no significant correlation between speaking performance and grammatical competence. However, FI students outperformed in speaking and FD students surpassed in grammar. In fact, those who scored higher on both tests used more SILLs than those who scored lower. Abstrak: Penelitian ini merupakan upaya untuk melihat hubungan antara kemampuan berbicara dan kompetensi gramatikal, khususnya dalam konteks EFL dengan memasukkan gaya belajar kognitif dan Strategy Inventory for Language Learning (SILL). Studi korelasional digunakan untuk menganalisis nilai tes berbicara argumentatif dan tata bahasa tertulis pada 30 mahasiswa Ilmu Ekonomi STIE Malangkuceswara Malang. Diketahui bahwa tidak ada korelasi yang signifikan antara kinerja berbicara dan kompetensi tata bahasa. Namun, siswa FI unggul dalam berbicara dan siswa FD melampaui dalam tata bahasa. Faktanya, mereka yang mendapat skor lebih tinggi pada kedua tes menggunakan lebih banyak SILL dibandingkan mereka yang mendapat skor lebih rendah.